2013
DOI: 10.1038/aps.2013.69
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interactions between 20(S)-ginsenoside Rh2 and the HIV protease inhibitor ritonavir in vitro and in vivo

Abstract: Aim: 20(S)-Ginsenoside Rh2 (Rh2) has shown potent inhibition on P-glycoprotein (P-gp), while most HIV protease inhibitors are both substrates and inhibitors of P-gp and CYP3A4. The aim of this study was to investigate the potential pharmacokinetic interactions between Rh2 and the HIV protease inhibitor ritonavir. Methods: The effects of Rh2 on the cellular accumulation and transepithelial transport of ritonavir were studied in Caco-2 and MDCK-MDR1 cells. Male rats were administered Rh2 (25 or 60 mg/kg, po) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…In addition to antiviral effects, ginseng interacts with antiHIV drugs and changes their pharmacokinetic properties. Shi et al [62] have reported that ginsenoside Rh2 increased the accumulation and decreased the efflux of ritonavir through P-glycoprotein (P-gp) in Caco-2 cells and MDCK-MDR1 cells. An in vivo study using rats confirmed that intravenous administration of ginsenoside Rh2 inhibited ritonavir efflux and increased the plasma level of ritonavir.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…In addition to antiviral effects, ginseng interacts with antiHIV drugs and changes their pharmacokinetic properties. Shi et al [62] have reported that ginsenoside Rh2 increased the accumulation and decreased the efflux of ritonavir through P-glycoprotein (P-gp) in Caco-2 cells and MDCK-MDR1 cells. An in vivo study using rats confirmed that intravenous administration of ginsenoside Rh2 inhibited ritonavir efflux and increased the plasma level of ritonavir.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…The rare ginsenosides 20(S)-Rh2, Rk2, and Rh3 have remarkable anti-cancer effects on various types of cancers [9,15], similar to that of ginsenoside C-K. In particular, the efficacy of 20(S)-Rh2, including anti-cancer, antihyperglycemic, and anti-obesity effects [26], has been reported in many previous publications. However, the production of high-purity ginsenoside Rh2 or its analogs (Rk2, Rh3) has been limited by a lack of ginsenoside transformation technology.…”
Section: Discussionmentioning
confidence: 81%
“…However, administration of 500 mg of ginseng (standardized to 5% ginsenosides) in healthy individuals for 4 wk increased CYP3A4 enzyme activity by approximately 34% [6] . In addition, ginsenoside metabolites have been reported to have the potential to inhibit P- glycoprotein (P-gp) [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%